Support in Work Context and Employees’ Well-Being: The Mediation Role of the Work- Family Conflict - Sousa, Claúdia; Chambel, Maria José; Carvalho, Vânia Sofia (Journal of Tourism, Sustainability and Well-being, 2018)
Changes in families and in the structure of the workforce have contributed to a change in traditional roles, leading to an increase of the number of men and women who simultaneously have family and work responsibilities. Because the workforce has different sources of support in the labor environment – organizational, supervisor, and coworker support – it becomes important to study the impacts that each of these sources of support has on workers’ general well-being and to understand whether the existent work-family conflict explains this relationship. Indeed, the present research aims to examine the relationship between perceived support and general well-being as well as the mediating effect of work-life conflict on this relationship. The data were collected from a company from the textile industry, composing a sample of 821 store operators. The results show that work-life conflict helps explain the relationship between support from the organization and coworkers and workers’ general well-being. However, supervisor support did not relate to work-family conflict. Based on the specific managerial characteristics of this company, some plausible explanations for these results are provided. Practical implications related to the results obtained are presented, in addition to the research limitations and suggestions for future research.